USPHS Corps Care: Force Health Protection for Public Health Officers During the Ebola and COVID-19 Responses. (March 2021) - Myles, Ian A.; Johnson, Daniel R.; Pham, Hanah; Adams, Ava; Anderson, Jerome; Banks-Shields, Marina; Battle, Andrea G.; Demby, Mary L.; Hastings, Deborah; Lewis, Robin Marie; Pauli, Ingrid B.; Vedder, Jennifer A.M.; et al.
Force health protection (FHP) is defined as "the prevention of disease and injury in order to protect the strength and capabilities" of any service population. FHP was the foundational principal of the US Public Health Service (USPHS). President John Adams' signing of An Act for Sick and Disabled Seamen on July 16, 1798, marked the first dedication of US federal resources to ensuring the well-being of US civilian sailors and Naval service members. On January 4, 1889, President Cleveland enacted the USPHS Commissioned Corps, creating the world's first (and still only) uniformed service dedicated to promoting, protecting, and advancing the health and safety of the United States and the world. Building on the lessons of the 2014-2015 response to the Ebola virus pandemic, the Corps Care program was formalized in 2017 to establish and implement a uniform and comprehensive strategy to meet the behavioral health, medical, and spiritual needs of all Commissioned Corps officers. Its role was expanded in response to the coronavirus disease 2019 (COVID-19) pandemic, which has placed unprecedented demands on health care workers and spotlighted the need for FHP strategies. We describe the FHP roles of the Corps Care program for the resiliency of Commission Corps officers in general and the Corps' impact during the response to the COVID-19 pandemic. Qualitative analysis of FHP discussions with deployed officers highlights the unique challenges to FHP presented by the pandemic response.